Bacterial community in alpine grasslands along an altitudinal gradient on the Tibetan Plateau. Issue 1 (2nd January 2014) - Yuan, Yanli; Si, Guicai; Wang, Jian; Luo, Tianxiang; Zhang, Gengxin
Abstract: The Tibetan Plateau, 'the third pole', is a region that is very sensitive to climate change. A better understanding of response of soil microorganisms to climate warming is important to predict soil organic matter preservation in future scenario. We selected a typically altitudinal gradient (4400 m–5200 m a.s.l) along south-facing slope of Nyainqentanglha Mountains on central Tibetan Plateau. Bacterial communities were investigated using terminal restriction fragment length polymorphism analysis (T-RFLP) combined with sequencing methods. Acidobacteria and Proteobacteria were dominant bacteria in this alpine soil. Redundancy analysis revealed that soil bacterial communities were significantly different along the large altitudinal gradient, although the dominant environmental driving factors varied at different soil depth. Specifically, our results showed that precipitation and soil were dominant environmental factors that influence bacterial communities at 0–5 cm depth along the altitudinal gradients, whereas pH was a major influential factor at 5–20 cm soil. In this semi-arid region, precipitation rather than temperature was a main driving force on soil bacterial communities as well as on plant communities. We speculate that an increase in temperature might not significantly change soil bacterial community structures along the large altitudinal gradient, whereas precipitation change would play a more important role in affecting soil bacterial communities. Abstract :